EFFICACY OF MODIFIED THERMAL BALLOON ABLATION IN HEAVY MENSTRUAL BLEEDING - Mubashra Naz; Faiza Irshad (Journal of University Medical & Dental College)
ABSTRACT Objective: To determine the efficacy of modified thermal balloon ablation using Foley’scatheter in the treatment of heavy menstrual bleeding. Design: Quasi experimental study. Setting: Department of obstetrics and gynaecology, University Medical and Dental College, Madina Teaching Hospital, Faisalabad. Methodology: Fifty three patients with heavy menstrual bleeding between 35 to 45 years of age underwent modified thermal balloon ablation using Foleys catheter. Patients were selected after complete clinical evaluation and investigations. Procedure was under taken in operation theater under saddle block .Three cycles of modified thermal balloon ablation using Foley’scatheter with hot saline were performed to ablate endometrium. Time given to each cycle was 7 minutes. Main outcome measures: Main outcome measures were reduction in menstrual flow, amenorrhea, minor short term side effects and need of hysterectomy after failure of procedure. Results: Sixty nine percent of patients experienced reasonable reduction in menstrual blood flow. Twelve percent had amenorrhea at the end of 6 months of follow up. Eighteen percent observed no change in bleeding pattern and underwent hysterectomy after failure of procedure. Six percent patients complained of minor side effects like abdominal pain and endometritis. Conclusions: Modified thermal balloon ablation with Foley’s catheter can be promising conservative management of heavy menstrual bleeding in resource poor settings. Reassuring results dictates that procedure can be adopted with reasonable confidence in future.